Genetic variants in TNFA, LTA, TLR2 and TLR4 genes and risk of sepsis in patients with severe trauma: nested case-control study in a level-1 trauma centre in SERBIA. Issue 3 (March 2021) - Djuric, Olivera; Andjelkovic, Marina; Vreca, Misa; Skakic, Anita; Pavlovic, Sonja; Novakovic, Ivana; Jovanovic, Bojan; Skodric-Trifunovic, Vesna; Markovic-Denic, Ljiljana
Highlights: Genetic variability in the innate immunity contributes to susceptibility and severity of sepsis after severe trauma. While variants in TNFA and LTA genes have been investigated in several studies, TLR2 and TLR4 have not yet been investigated in trauma patients. We assessed association between 8 single nucleotide variants (SNV) within TNFA, LTA, TLR2 and TLR4 genes and risk of posttraumatic sepsis. Rare allele carriage within TNFA rs1800629 and TLR4 rs4986791 genetic variants confer significant risk of posttraumatic sepsis. TLR4 gene variants (rs4986790 and rs4986791) have been labelled by in silico programs as disease causing. Abstract: Introduction : Single nucleotide variants (SNVs) represent important genetic risk factors for susceptibility to posttraumatic sepsis and a potential target for immunotherapy. We aimed to evaluate the association between 8 different SNVs within tumor necrosis factor alpha ( TNFA ), lymphotoxin alpha ( LTA ) and Toll-like receptor ( TLR2 and TLR4 ) genes and the risk of posttraumatic sepsis. Methods : Nested case-control study was conducted in the emergency department of the Clinical Centre of Serbia including 228 traumatized patients (44 with sepsis and 184 without sepsis). To compare the results of trauma subjects with the data from the general population, a control group of 101 healthy persons was included in the study. Genotyping of TNFA (rs1800629 and rs361525), LTA (rs909253), TLR2 (rs3804099, rs4696480 and rs3804100), and TLR4 (rs4986790 and rs4986791) was performed for all patients within all three groups using the real-time PCR method. MutationTaster database and in silico software SIFT were used to predict the variant pathogenic effect. Results : Carriage of the G allele of the TNFA rs1800629 gene variant (OR 2.1, 95%CI 1.06-4.16) and T allele-carriage of the TLR4 rs4986791 genetic variant (OR 3.02, 95%CI 1.31-6.57) were associated with significantly higher risk of sepsis in trauma patients when compared to the general population prone to sepsis and traumatized patients without developing a sepsis, respectively. Of these two variants, only variant in TLR4 gene (rs4986791) has been labeled as disease causing by both the MutationTaster database and the in-silico software SIFT, which further supports the role of this variant in various pathologies including sepsis. For the remaining six variants no significant association with the susceptibility to sepsis was detected. Conclusions : Carriage of the G allele of the TNFA rs1800629 gene variant and T allele-carriage of the TLR4 rs4986791 genetic variant confer significant risk of posttraumatic sepsis. TLR4 gene variants (rs4986790 and rs4986791) has been labelled as disease causing.